Effects of the immobilization of recombinant Escherichia coli on cyclodextrin glucanotransferase (cgtase) excretion and cell viability - Mohd Fuzi, Siti Fatimah Zaharah; Md Illias, Rosli; Ghazali, Nazlee Faisal; Ismail, Ahmad Fauzi; Che Man, Rohaida (Elsevier Ltd., 2015)
The excretion of recombinant enzymes is a preferred approach for protein expression because of the associated high level of expression, low level of proteolysis, ease of purification and more favorable folding environment. However, cell lysis is one of the major drawbacks in the excretion of enzymes when using Escherichia coli as a host. In this study, the effects of different polymer of hollow fiber membrane and culture conditions on the enzyme excretion, cell lysis and plasmid stability of immobilized E. coli were investigated. The cells immobilized on a hollow fiber membrane composed of a polyvinylidene fluoride (PVDF) polymer exhibited a 2–4-fold increase in CGTase excretion, over a 100% increase in plasmid stability and 28-60% reduction in cell lysis compared with free cells. Hence, the immobilization of E. coli using a hollow fiber membrane was demonstrated to increase enzyme excretion and cell stability.